Records Life Cycle and Functional Activities for Landscaping Electronic Management Systems in the Fourth Industrial Revolution - Marutha, Ngoako Solomon (Mousaion: South African Journal of Information Studies, 2023)
Developing an electronic records management system has always been challenging for most organisations, healthcare fraternity not excluded. The paper sought to investigate the landscaping of electronic systems using functional patient records management activities and life cycle. The rationale is to share views and guide organisations that are struggling with providing specifications for a functional records management system. The study used a qualitative approach to apply the literature in supporting the views about landscaping electronic systems by using functional records management activities and life cycle. The study revealed that without consideration of records management activities, the likelihood is that the system may not be properly functional. The best way to landscape an electronic system for records management is to use records management activities and life cycle. This will assist in avoiding critical omissions to ensure that all records management system operational activities are included. The paper is proposing a new way of landscaping the electronic system by using the records management functional activities and life cycle. It also provides a framework to guide the implementers or electronic system developers.